A user’s guide to data from Round 2 of the Pakistan Rural Household Panel Survey (PRHPS) 2013 - International Food Policy Research Institute; Innovative Development Strategies (International Food Policy Research Institute, 2016)
Responding to a request from the Government of Pakistan, the Pakistan Strategy Support Program (PSSP) was launched in July 2011. This program is a flexible country-led and country-wide policy analysis and capacity strengthening program, which provides analytical support on a range of economic policies affecting agricultural growth and food security in the country. The core purpose of the program is to contribute to pro-poor economic growth and enhanced food security through strengthened national capacity for designing and implementing evidence-based policy reforms. PSSP’s four primary research priorities are as follows: a. Agricultural production and productivity; b. Water management and irrigation; c. Macroeconomics, markets and trade; d. Poverty reduction (Income dynamics) and job creation (social safety nets). The Rural Household Panel Survey (RHPS) aims to provide quantitative bases to identify and address these four primary research priorities. The RHPS covers 2090 households in 76 primary sampling units in the rural areas of three provinces: (i) Punjab; (ii) Sindh; and (iii) Khyber Pakhtunkhwa (KPK). The sample is nationally representative of the rural areas of the three provinces. This survey collected information on a large number of topics such as: sources of income, nature of employment, consumption patterns, time use, assets and savings, loans and credit, education, migration, economic shocks, and participation in social safety nets. Four survey instruments were used to collect this information in Round 2. These included two household level questionnaires (to collect household information on various household and individual level aspect by males and females separately), a community questionnaire, and a price questionnaire.